Management of MDR and XDR TB - Boeree, Martin (Henry Stewart Talks, 2014)
Management of multi drug resistance (MDR) and extensive drug resistance (XDR) TB, Management of TB before era of drug treatment, Surgery for TB, Drug treatment was introduced from 1943-1963, Rifampicin (1963), Timeline: discovery of drugs for TB, Emergence of totally drug resistant TB – Epidemiology, Outcomes of MDR-TB treatment, Survival curve of HIV patients with XDR TB, Current drug treatment, Treatment outcome in several cohorts, Death rates in several cohorts, Current approach for treatment of MDR/XDR TB, WHO's programmatic management of DR TB, Treatment recommendations, Group 1: oral first-line agents, Group 2: fluoroquinolones, Group 3: injectables, Group 4: less-effective anti-TB drugs, Group 5: less-effective or clinical data sparse drugs, Future drug treatment, New compounds, Bedaquiline (TMC207), The nitroimidazoles – Thioridazine, NC-001 (PA-824, moxifloxacine, PZA), Dreams and realities for the future of TB treatment
Updated at 2014/05/12